DEVELOPMENT OF LEARNING MEDIA ROTAR (ROTATING WHEEL) IN CLASS V MATHS LESSON AT SDN 101866 BATANG KUIS PEKAN - Pasaribu, Juli Indah Sari; Hariati, Emy; Ramadianti, Astria Ayu (Transpublika Publisher, 2024)
This study aims to develop learning media for rotating wheels to students and to determine the feasibility of using the media. to determine the feasibility of using the media, as well as knowing the level of validity of the media through the responses of educators and students after using the media. media through the responses of educators and students after using the wheel learning media. learning media. This type of research is a development research (R&D) with the ADDIE development model which consists of the stages of analysis, design, development, implementation, evaluation. The subjects of this study were grade V grade students at SD Negeri 101866 Batang Kuis, totalling 24, consisting of 7 girls and 17 boys. The results of research and development obtained a design in the form of a rotating wheel learning media in mathematics learning in class V SDN 101866 Batang Kuis Pekan obtained a score of feasibility value of 80% by material experts and 92% by media expert. Student response to media feasibility obtained an average score of 92%. Based on the results of the description above Based on the results of the description above, the product developed by the researcher is feasible and valid to be used as a learning media.